Isolation of dacrocystitis causing bacteria among the patients of East Godavari district, Andhra Pradesh (Bangladesh Journal of Medical Science, 2016)
Introduction: Inflammation of the lacrimal sac, dacryocystitis is one of the important causes of ocular morbidity in Indian subcontinent.Objective: To isolate and identify the aerobic bacterial pathogens associated with dacryocystitis and to determine their antibacterial sensitivity pattern.Materials and methods: A total of 304 individuals were included in the study. Blocked tissue / pus was collected and microbial analysis was done.Results: Infection rate was more in the female than male, statistically highly significant (p